2020
DOI: 10.1128/jmbe.v21i2.1987
|View full text |Cite
|
Sign up to set email alerts
|

M-LoCUS: A Scalable Intervention Enhances Growth Mindset and Internal Locus of Control in Undergraduate Students in STEM

Abstract: Student self-beliefs regarding intelligence and ability have been shown to correspond to achievement and persistence in an academic domain. Specifically, previous research has suggested that a growth mindsetor the belief that intelligence is malleable and can increase with effort-is associated with student success. Locus of control is a related but distinct self-belief regarding personal agency over various academic and nonacademic outcomes and has also been associated with study skills and academic persistenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
(49 reference statements)
1
11
0
Order By: Relevance
“…When talking about student-level factors, we need to be careful. For example, Nallapothula et al ( 71 ) chose a framework to explain college students’ academic outcomes (e.g., grades and persistence) that balances students’ beliefs about themselves, as measured by growth mindset, and their assumptions about agency. They caution that students with a growth mindset may still experience academic hardship or dropout because they face “institutional barriers, such as institutionalized racism” ( 71 ).…”
Section: Emergent Conceptual Categories From the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…When talking about student-level factors, we need to be careful. For example, Nallapothula et al ( 71 ) chose a framework to explain college students’ academic outcomes (e.g., grades and persistence) that balances students’ beliefs about themselves, as measured by growth mindset, and their assumptions about agency. They caution that students with a growth mindset may still experience academic hardship or dropout because they face “institutional barriers, such as institutionalized racism” ( 71 ).…”
Section: Emergent Conceptual Categories From the Literaturementioning
confidence: 99%
“…For example, Nallapothula et al ( 71 ) chose a framework to explain college students’ academic outcomes (e.g., grades and persistence) that balances students’ beliefs about themselves, as measured by growth mindset, and their assumptions about agency. They caution that students with a growth mindset may still experience academic hardship or dropout because they face “institutional barriers, such as institutionalized racism” ( 71 ). Explicit caveats such as these and careful choice of inclusive frameworks help to situate student-level interventions within the system of barriers and offer appropriate contrast for the different ways in which we can approach DEI.…”
Section: Emergent Conceptual Categories From the Literaturementioning
confidence: 99%
“…Moreover, reducing catastrophizing tendencies, for example via smartphone-based cognitive behavioral interventions for mental health prevention (Ebert et al, 2018;Marciniak et al, 2020), increasing internal locus of control, e.g., via online interventions as has been done by Nallapothula et al (2020) in an academic context, increasing optimism, e.g. using the Best Possible Self intervention (Malouff & Schutte, 2017), and learning to also see positive aspects in the overall challenging situation, e.g., via mobile cognitive behavioral interventions (Ebert et al, 2018;Marciniak et al, 2020) are promising paths to increase individual well-being.…”
Section: Discussionmentioning
confidence: 99%
“…14,19,20 Prior studies in nursing and undergraduate students suggest several strategies may be utilized and assessed among pharmacy students to improve internal locus of control, which may ultimately reduce stress and/or benefit academic performance. [71][72][73] These strategies include problem-based education to encourage problem-solving and self-directed learning; online videos discussing locus of control and growth mindset and how they may be utilized by students during their education; and mentoring programs to build supportive and nurturing connections. [71][72][73] For example, Demir et al 71 found that a peer mentoring program among nursing students, in which fourth-year students served as mentors for first-year students, contributed to increased internal locus of control and improved ability to cope with stress among the first-year students.…”
Section: A J P Ementioning
confidence: 99%
“…[71][72][73] These strategies include problem-based education to encourage problem-solving and self-directed learning; online videos discussing locus of control and growth mindset and how they may be utilized by students during their education; and mentoring programs to build supportive and nurturing connections. [71][72][73] For example, Demir et al 71 found that a peer mentoring program among nursing students, in which fourth-year students served as mentors for first-year students, contributed to increased internal locus of control and improved ability to cope with stress among the first-year students. These first-year students described their mentors as providing support, motivation, and guidance, which increased self-confidence and self-awareness.…”
Section: A J P Ementioning
confidence: 99%